A review of the automated guided vehicle systems: dispatching systems and navigation concept - Bourafa, Rami; Siegfried, Patrick; Арафа, Рамі; Зігфрід, Патрік (Харківський національний автомобільно-дорожній університет, 2023)
Problem. As one of the three key elements of flexible manufacturing systems (FMS), automated guided vehicles (AGVs) play a significant role in material handling systems. They've been around for more than a decade, primarily in Europe. AGVs were formerly utilized mostly in production lines, but due to recent industrial development, they now play a vital role in a variety of different applications and domains, including warehouses, port facilities, transportation systems, and even the medical sector. Goal. The purpose of the work is to analyze two methods of AGV control and the paths that the AGV should follow during transport operations, taking into account safety and limitations for heavy loads that need to be transported in difficult conditions. Methodology. We attempted to provide a summary of the two existing AGV control methods, centralized and decentralized control offered by major manufacturers in this study. Almost all function in a centralized manner, with a single central controller controlling the whole fleet of AGVs. The author sees a tendency toward decentralized systems in which AGVs make individual decisions in favor of transportation flexibility, robustness, and adaptability. A brief explanation of well-known and mature navigation technologies used by AGVs in the industry is also provided, along with both physical and virtual paths to be followed by the AGV during transportation operations, since these technologies get to be a key issue given the safety constraints, particularly for heavy loads to be transported in challenging environments. Results. This paper covers one of the key tasks that must be completed in order to control an AGV system for a central and decentral architecture, for which we have already given a broad overview, as well as the differences between the architectures and their benefits and drawbacks. Originality. The author sees that the merging of various techniques we have will lead to more and new challenges as well as innovations, however, that practical application of distributed control still requires further research and studies and has a way to go in terms of taking other sections such as safety and sustainability into account. Practical value. The primary benefits and drawbacks of various technologies are discussed, as well as how we might improve the efficiency of some of them.
Огляд автоматизованих керованих транспортних систем: системи диспетчеризації та концепція навігації
Keywords: Automated guided vehicles; control techniques; localization; centralized; decentralized; автоматизовані керовані транспортні засоби; техніка контролю; локалізація; централізація; децентралізація; 629; 10.30977/AT.2219-8342.2023.52.0.09